Utilizar corpus informáticos con un público Lansad (lenguas para especialistas de otras disciplinas) - Eva Schaeffer-Lacroix (ALSIC: Apprentissage des Langues et Systèmes d'Information et de Communication)
Since the eighties, the use of corpora for language learning has been defended by researchers, such as Johns (1991). This idea is supported by the assumption that the texts the learners deal with represent an important factor for language learning. In general, the quantity of the input is quite restricted, and, even if the data are digitized, they tend to be static and cannot be easily manipulated by the reader. Learners could benefit from big data (i.e., from corpora containing text collections) which can be explored in a targeted way. This paper aims to present some conceptual and technical aspects likely to assist foreign language teachers wishing to use corpora with their students. It describes step by step how to create, digitize and explore corpora. The illustrating examples are mainly provided in German and some are in English.